2016
DOI: 10.14744/tej.2016.21939
|View full text |Cite
|
Sign up to set email alerts
|

Foreign material in a maxillary sinus as a complication of root canal treatment: a case report

Abstract: E ndodontic infections of posterior maxillary teeth The roots of maxillary teeth proximity to maxillary sinuses can lead to overfilling of endodontic materials to maxillary sinuses accidentally. In some cases, overfilling of endodontic materials require surgical procedures. Foreign endodontic material within the maxillary sinus after endodontic treatment on extracted tooth #15 is presented in this case report. Foreign material inside the maxillary sinus was removed successfully by Caldwell-Luc operation. Posto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…On review of literature, the majority of iatrogenic cases are caused by the presence of tooth implants (54%) [ 11 ], tooth root [ 12 14 ], and surgical bur [ 15 ] ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…On review of literature, the majority of iatrogenic cases are caused by the presence of tooth implants (54%) [ 11 ], tooth root [ 12 14 ], and surgical bur [ 15 ] ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The proximity of the maxillary teeth to the maxillary sinuses may cause the endodontic materials to accidentally overflow the maxillary sinuses. [9] Literature results have shown that dental fillings with maxillary sinus can develop inflammation necrosis and FB in the maxillary sinus. Recent studies have shown that the risk of FB 14 times more than the patients without endodontic treatment in patients treated endodontically in the upper molar, premolars and canine teeth.…”
Section: Discussionmentioning
confidence: 99%